2005
DOI: 10.1073/pnas.0503381102
|View full text |Cite
|
Sign up to set email alerts
|

Protein fucosylation regulates synapsin Ia/Ib expression and neuronal morphology in primary hippocampal neurons

Abstract: Although fucose-␣(1-2)-galactose [Fuc␣(1-2)Gal] carbohydrates have been implicated in cognitive processes such as long-term memory, the molecular mechanisms by which these sugars influence neuronal communication are not well understood. Here, we present molecular insights into the functions of Fuc␣(1-2)Gal sugars, demonstrating that they play a role in the regulation of synaptic proteins and neuronal morphology. We show that synapsins Ia and Ib, synapse-specific proteins involved in neurotransmitter release an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 38 publications
5
97
0
1
Order By: Relevance
“…The mean area intensity of NG2-positive cells was determined to be twofold to threefold higher than that measured for NG2-negative cells. (Murrey et al, 2006). Here, we showed that synapsin I carries Lewis x also on O-glycans and oligomannoses on N-glycans.…”
Section: Synapsin Is Expressed By Glial Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…The mean area intensity of NG2-positive cells was determined to be twofold to threefold higher than that measured for NG2-negative cells. (Murrey et al, 2006). Here, we showed that synapsin I carries Lewis x also on O-glycans and oligomannoses on N-glycans.…”
Section: Synapsin Is Expressed By Glial Cellsmentioning
confidence: 85%
“…These results show that synapsin carries N-glycans and, thus, is a glycoprotein. Since synapsin has been reported to carry fucose in ␣1,2-linkage to galactose (Murrey et al, 2006) and we showed that it carries oligomannose, we further characterized the glycosylation of purified synapsin using carbohydrate-specific antibodies and lectins. No synapsin staining was observed with antibodies recognizing the HNK-1 epitope or polysialic acid, while L5 antibody, which recognizes Lewis x , bound to synapsin (Fig.…”
Section: Synapsin Is a Glycoproteinmentioning
confidence: 99%
“…The galactose-containing disaccharide, fucose-␣(1-2)galactose, has been implicated in memory formation, learning, and synaptic plasticity (15)(16)(17)(18)(19)(20)(21). Fucose-␣(1-2)galactose sugars are enriched on glycoproteins in presynaptic nerve terminals (22), and it has been shown that fucose-␣(1-2)-galactose modification has profound effects on the expression and degradation of the synaptic vesicle-associated protein, synapsin (22). Furthermore, the importance of galactose for normal neuronal function is indicated by the fact that B27, the widely used serum replacement for primary neuronal cultures, contains galactose (23).…”
Section: Discussionmentioning
confidence: 99%
“…Because 14-3-3s might promote interaction of SORLA with synapsin in a phosphorylation-dependent manner, we propose the existence of a tripartite complex that regulates phosphorylation-dependent degradation of synapsins. Based on our data, complex formation identifies phospho-synapsin molecules destined for calpain-mediated degradation, a major pathway for control of synapsin turnover [19]. Importantly, shRNA-mediated knockdown of calpain in SH-SY5Y cells levitated the effect of SORLA overexpression on synapsin levels (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Synapsin levels were substantially reduced in SY5Y-S compared to parental SY5Y cells ( It has been shown before that turnover of synapsin is controlled by the calcium-activated protease calpain [19]. To evaluate whether the SORLA-dependent reduction of synapsin levels was mediated by this protease, we generated cell clones from SY5Y and SY5Y-S lines stably overexpressing a small hairpin (sh) RNA directed against calpain 1.…”
Section: Sorla Regulates Synapsin Expression Through Calpain Activitymentioning
confidence: 99%